Hsa-miR-21 promoted the progression of lung adenocarcinoma by regulating LRIG1 expression - Li Liu; Xinhua Liu; Chengpeng Gao; Meijuan Liu; Mengmeng Peng; Leqiang Wang (BMC Pulmonary Medicine)
Abstract Lung cancer is the foremost cause of cancer-related fatalities globally, and lung adenocarcinoma (LUAD) is one of the common types of lung cancer with significant molecular heterogeneity. Leucine rich repeats and immunoglobulin like domains 1 (LRIG1) has been demonstrated to be down-regulated in lung cancer and related to prognosis of patients. The purpose of this work is to explore the targeting miRNAs of LRIG1, and the related regulatory mechanisms in LUAD. The data of LUAD patients were collected from The Cancer Genome Atlas and Gene Expression Omnibus databases. The differential expression analysis and gene set enrichment analysis (GSEA) were performed using “limma” and “clusterProfiler” function package, respectively. The levels of hsa-miR-21 mRNA and LRIG1 mRNA and LRIG1 protein expressions were analyzed using RT-qPCR and western blot analysis. The infiltration of immune cells was determined using CIBERSORT software. In LUAD patients, hsa-miR-21 expression was observably related to LRIG1 expression. Hsa-miR-21 might negatively modulate the LRIG1 expression in LUAD. LUAD patients with hsa-miR-21 up-regulation exhibited inferior prognosis. In addition, those with LUAD who had high hsa-miR-21 expression but low LRIG1 expression had a worse prognosis, whereas those with low hsa-miR-21 expression but high LRIG1 expression had a better prognosis. Functional enrichment analysis indicated that metabolic related signaling pathways (EGFR tyrosine kinase inhibitor resistance) were significantly activated in LUAD patients with LRIG1 up-regulation. Finally, we found that relative content of naive B cells, plasma cells and resting CD4 + T cells were significantly increased and regulatory T cells and Macrophages M0 were decreased in LRIG1 high expression group and hsa-miR-21 low expression group. We firstly reported that hsa-miR-21 might regulate the LRIG1 expression in LUAD, thereby effecting the onset and progression of LUAD. Clinical trial number: Not applicable.